1996
DOI: 10.1111/j.1600-0404.1996.tb05880.x
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing compensatory task conditions for episodic memory in Alzheimer's disease

Abstract: Numerous recent studies have addressed the question of whether memory can be improved in patients with Alzheimer's disease (AD). Evidence from both experimental studies and intervention work suggests that AD exerts a substantial effect not only on memory functioning in general, but also influences the potential for memory improvement. Contrary to previous claims, however, several recent studies indicate that AD patients can utilize cognitive support to improve memory under certain conditions. To achieve perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 36 publications
1
32
0
1
Order By: Relevance
“…To be successful, intervention should be fairly prolonged, lasting weeks to months with regular sessions (Ba Èckman, 1996). However, the increasingly tight control of (para)medical professionals' time and the need for cost-effective mental healthcare delivery has rendered extensive memory rehabilitation programmes an extremely dif®cult enterprise.…”
Section: Methodology Of Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…To be successful, intervention should be fairly prolonged, lasting weeks to months with regular sessions (Ba Èckman, 1996). However, the increasingly tight control of (para)medical professionals' time and the need for cost-effective mental healthcare delivery has rendered extensive memory rehabilitation programmes an extremely dif®cult enterprise.…”
Section: Methodology Of Interventionmentioning
confidence: 99%
“…The presence of impaired learning abilities is a hallmark feature of AD, and broadly conceptualised as the amnesia±dysexecutive syndrome (Becker, 1987) has refrained many investigators from including memory rehabilitation in non-drug treatment programmes for AD patients . For instance, the traditional encoding and retrieval strategies, which require intact learning and other preserved cognitive resources, and which have proved variously bene®cial for non-demented older individuals with age-related memory loss (Brooks et al, 1999), are considered not applicable to AD patients (Ba Èckman, 1996). Indeed, non-responsiveness in elderly subjects to these training programmes has been proffered as a promising diagnostic strategy for early identi®cation of impending AD (De Vreese and Neri, 1997).…”
Section: Scepticism Towards Memory Rehabilitation In Admentioning
confidence: 98%
“…Despite the memory deficits associated with AD, the facilitation of episodic memory can be used when adequate support is provided (Backman and Dixon, 1992;Backman, 1996).…”
Section: Frontiers In Human Neurosciencementioning
confidence: 99%
“…A different method is applied for the treatment of memory in AD patients during errorless learning because some previous studies have suggested that cognitive rehabilitation approaches may have positive effects on memory functioning during the earlystages of AD (Backman and Dixon, 1992;Backman, 1996;Clare et al, 1999Clare et al, , 2000Clare et al, , 2001Clare et al, , 2002Clare et al, , 2003aClare et al, , 2009). This technique employs learning conditions in which patients are prevented from making errors and is based on various techniques (e.g., vanishing cues and spaced retrieval) that have been previously described for MCI studies.…”
Section: Frontiers In Human Neurosciencementioning
confidence: 99%
“…Until relatively recently, it was widely held that "all efforts to enhance memory in Alzheimer's disease may be unsuccessful" (Dick, Kean & Sands, 1989). However, growing empirical research has led some researchers to suggest that there may after all be potential for improving memory skills and cognitive functioning in people with Alzheimer-type and other dementias through provision of appropriate support (Bäckman, 1996), while others propose that certain linguistic skills, for example phonology and reading (Law & O' Carroll, 1998) can escape deterioration, calling them "islands of retained abilities" (Bohling, 1991). Latterly, efforts have focussed on maintaining these core functions for as long as possible, adopting methods such as "reality orientation" and memory exercises.…”
Section: Introductionmentioning
confidence: 98%